2018
DOI: 10.21037/jtd.2018.05.14
|View full text |Cite
|
Sign up to set email alerts
|

On-pump beating heart versus conventional coronary artery bypass grafting: comparative study on early and long-term clinical outcomes

Abstract: The OPB strategy may be as safe and effective as the conventional strategy during CABG among patients with similar risk profiles. A prospective randomized trial is warranted to better ascertain the beneficial impact of OPB-CABG as both a viable and a durable alternative strategy to C-CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…So a new hybrid method, the on-pump beating-heart [6] (OPBH) CABG, has been used in these high-risk patients in recent years [7,8] . This technique could maintain the coronary blood flow to reduce myocardial injury [9] and reduce the preload and afterload to decrease myocardial oxygen demand.…”
Section: Introductionmentioning
confidence: 99%
“…So a new hybrid method, the on-pump beating-heart [6] (OPBH) CABG, has been used in these high-risk patients in recent years [7,8] . This technique could maintain the coronary blood flow to reduce myocardial injury [9] and reduce the preload and afterload to decrease myocardial oxygen demand.…”
Section: Introductionmentioning
confidence: 99%
“…As a conclusion, both these techniques scored even and the decision rested upon the surgeon to choose the most appropriate technique. Another new study showed that the use of CPB support makes ON-BH CABG technically similar to C-CABG, and there were no obvious clear differences between these two strategies either short or long term [15]. We would like to state here that it should be however considered that technically and biochemically, ON-BH CABG differs from classical C-CABG in that there is no aortic cross clamping, rendering the procedure more physiological.…”
Section: Discussionmentioning
confidence: 84%
“…Scientific evidence on the topic derives from retrospective observational studies mainly focused on high-risk patients. Literature search yielded a total of 279 records, and 17 studies 7,10,13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28] and two meta-analyses 29,30 published between 2000 and 2020 were finally included in the systematic review (PRISMA flow diagram, Figure 1). Quality assessment is shown in Table 2; study characteristics and collected outcomes are summarized in Tables 3 and 4 and described below.…”
Section: Resultsmentioning
confidence: 99%
“…10,18,20,[24][25][26] Generalized data from all-comers population might support the idea of using OPBHC also in unselected patients. 7,15,19,23 Certainly, this hypothesis should be adequately investigated in future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation